2017
DOI: 10.1111/1440-1681.12882
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐contractile effects of perivascular adipose tissue in thoracic aorta from rats fed a high‐fat diet: role of aerobic exercise training

Abstract: The aim of the present study was to evaluate the effects of aerobic exercise training on perivascular adipose tissue (PVAT) function in thoracic aorta from rats fed a high-fat diet. Aortic vascular reactivity was performed in sedentary (SD), trained (TR), sedentary high-fat diet (SD-HF), and trained high-fat diet (TR-HF) male Wistar rats in the absence (PVAT-) or in the presence (PVAT+) of thoracic PVAT. We also measured circulatory concentrations of leptin and tumour necrosis factor alpha (TNF-α), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…To date, only two other studies have examined the effect of Ex on PVAT regulation of vascular function. In the previous studies, no effect of Ex on tPVAT mediated EDD were found in healthy rats [65], or in a rat model of diet induced obesity [66]. One potential reason for the different results is that the current study incorporated a vertical work component utilizing a 5% incline compared to 0%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To date, only two other studies have examined the effect of Ex on PVAT regulation of vascular function. In the previous studies, no effect of Ex on tPVAT mediated EDD were found in healthy rats [65], or in a rat model of diet induced obesity [66]. One potential reason for the different results is that the current study incorporated a vertical work component utilizing a 5% incline compared to 0%.…”
Section: Discussionmentioning
confidence: 78%
“…One potential reason for the different results is that the current study incorporated a vertical work component utilizing a 5% incline compared to 0%. In the diet induced obesity study [66], obesity did not impair the tPVAT-aorta relaxation relationship, therefore the effects of Ex in preventing or reversing disease mediated tPVAT dysfunction could not be evaluated and further highlights the novelty in the present data.…”
Section: Discussionmentioning
confidence: 96%
“…Aerobic exercise training stimulates angiogenesis in adipose tissue and PVAT, which improves blood flow, reduces hypoxia and macrophage infiltration [118], and improves vascular function [119]. The beneficial effects of exercise training may be attributed to the normalization of eNOS activity [120] or the reduction of iNOS expression in PVAT [121]. Exercise training can increase eNOS and phospho-eNOS expression in both the vascular wall and the PVAT, as well as increase adiponectin in the PVAT and reduce ROS in the vascular wall [120].…”
Section: Improving Enos Functionalitymentioning
confidence: 99%
“…Recently, the significance of exercise is increasingly recognized, so research groups started to use chronic exercise animal model in their studies. After male Wistar rats were trained on a treadmill designated for small animals with individual lanes for about 8 weeks, the thoracic aortae with PVAT were isolated for vascular function assay [44,45]. However, routine exercise results in broad effects in metabolic profile of trained animals that it may not be easy to draw a direct link between PVAT and the improved vascular function.…”
Section: Pretreatment Protocolmentioning
confidence: 99%